2020
DOI: 10.3389/fbioe.2020.00071
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium oxysporum and Aspergillus sp. as Keratinase Producers Using Swine Hair From Agroindustrial Residues

Abstract: Technological processes mediated by microorganisms and enzymes are promising alternatives for treatment of recalcitrant residues. Keratinases hydrolyze keratin, the primary component of some wastes generated in many industrial activities. The present study was designed to evaluate strategies for obtaining keratinases produced by fungi using submerged fermentation and two residues as substrates, chicken feathers and swine hair. Two fungi isolated from feather residues showed potential for keratinase production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Fundamentally, microbial keratinolysis is a proteolytic process as keratin is a protein. The microorganisms produce keratinolytic protease through feather degradation and also release thiol group during microbial growth supports the essential role of disulfide bond reduction (Preczeski et al, 2020). The feather degradation appeared to be related to an increase of soluble protein which indicates that degradation of feather by depends on growth of fungi.…”
Section: Influence Of Feather Concentration and Substrates On Fungal ...mentioning
confidence: 73%
See 1 more Smart Citation
“…Fundamentally, microbial keratinolysis is a proteolytic process as keratin is a protein. The microorganisms produce keratinolytic protease through feather degradation and also release thiol group during microbial growth supports the essential role of disulfide bond reduction (Preczeski et al, 2020). The feather degradation appeared to be related to an increase of soluble protein which indicates that degradation of feather by depends on growth of fungi.…”
Section: Influence Of Feather Concentration and Substrates On Fungal ...mentioning
confidence: 73%
“…Ai and Cic (2019) isolated and identified A. niger and Penicillium purpurogenum from Nigerian soil with keratin degrading potential by skim milk casein hydrolyzed by halo zones of hydrolysis (62 mM and 64 mM) and keratinase activity were recorded (13.5 and 12.0 U ml -1 ) by hydrolyzed human hair and chicken feather into reducing sugar and proteins. Preczeski et al (2020) reported that Aspergillus sp. showed higher enzymatic activity on 9 th day of fermentation where degradation was maximum (113.50 U ml -1 ) with feather as the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The autoclaved medium was inoculated with 1 mL bacterial cell suspension (1 mL of 24 h old bacterial suspension grown in 5 mL of the nutrient broth medium at 30 • C). The cultures were incubated at 37 • C under shaking at 270 rpm for 72 h. Keratinase activity of culture filtrate was assayed using a modified protocol of Preczeski et al [21] with keratin azure as a substrate. The reaction mixture contained 0.4 mL of crude enzymes and 1.6 mL of 0.4% keratin azure (Sigma K8500, Saint Louis, MI, USA) in 10 mM tris HCl (pH 8.5) buffer incubated at 50 • C for 1 h. Subsequently, the reaction was stopped with 0.8 mL of 10% trichloroacetic acid (TCA) then centrifuged at 5000 rpm for 20 min.…”
Section: Bacterial Isolation Screening For the Keratinolytic Activity And Keratinase Assaymentioning
confidence: 99%
“…Such procedures, however, should not impede progress in wider aspects of Neocallimastigomycota biology. Indeed, the use of alphanumeric designations to identify strains has been a long-standing and widely accepted approach in the fields of biotechnology [30][31][32][33], biochemistry [34][35][36], cell biology [37,38] and beyond.…”
Section: Biogeography and Ecological Distributionmentioning
confidence: 99%